Analysis Of Determinants Of Human Development Index Of City Districts In Central Java - Rifki Khoirudin; Nur Wahyumiani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Human development is part of the development process to create a dynamic generation in the mastery of science and technology that continues to be dynamic in order to create superior resources and determine the direction of life, which is shown through its human development index. The purpose of the following research is as an indicator to see what factors can be expected to affect the Human Development Index (HDI), and to find out how much the cause of GRDP, Minimum Wage, District, Population Growth, Poverty, and there is also the Average Years of Schooling in Central Java Province for the 2015-2020 period. The effort obtained on the GRDP, UMK, PJP, RRLS variables has t-statistics > t-table with a positive sign, meaning that these two variables have a positive and significant effect on the Human Development Index variable. The results of the research show that the poverty variable has a t-statistic > t-table with a negative sign, meaning that the poverty variable has a negative and significant influence on the Human Development Index variable.